Development of speed, agility, and quickness training model in soccer for learning to train age group based on an articulate storyline - Ikhsan, Syahrul Maulana; Widiawati, Prisca; Rahayuni, Kurniati (Bravo's : Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2023)
This research aims to develop a training model for speed, agility, and quickness in the sport of soccer for children in the learning to train age group using the Articulate Storyline learning media. The subjects of this research are 15 students aged 9-12 from SSB Bina Sakti in Rembang Regency. The data collection method used is a questionnaire containing closed and open-ended questions. Quantitative analysis is used to analyze the data. The results of the validation recapitulation show that soccer coaching experts and soccer experts gave a validation score of 94.8%, while the media expert gave a score of 76.4%. Based on the validation results from experts and group testing, it can be concluded that the development model for speed, agility, and quickness training in soccer presented through the Articulate Storyline learning media is highly valid and suitable for use in SSB Bina Sakti in Rembang Regency